2011
DOI: 10.1177/0194599810393117
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Identification Analysis of Total Laryngectomy

Abstract: Objectives To understand the contribution of intraoperative and postoperative hospital costs to total hospital costs, examine the costs associated with specific hospital services in the postoperative period, and recognize the impact of patient factors on hospital costs. Study Design Case series with chart review. Setting Large tertiary care teaching hospital system. Subjects and Methods Using the Pittsburgh Head and Neck Organ-Specific Database, 119 patients were identified as having total laryngectomy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 8 publications
(14 reference statements)
2
17
0
1
Order By: Relevance
“…Permanent salivary leakage from the communication leads to ongoing inflammation that inhibits proper wound healing and the onset of complementary therapy. This prolongs hospitalization, increases the costs of treatment, and, most importantly, strains the patient's physical and psychological well-being [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Permanent salivary leakage from the communication leads to ongoing inflammation that inhibits proper wound healing and the onset of complementary therapy. This prolongs hospitalization, increases the costs of treatment, and, most importantly, strains the patient's physical and psychological well-being [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, on multivariate analysis, treatment-related hospitalizations and emergency room visits did not significantly correlate with increased charges (p=0.145 and p=0.290, respectively). Others have identified intensive care unit stays as having the greatest impact on cost 10 and none of our patients required an intensive care unit stay.…”
Section: Discussionmentioning
confidence: 86%
“…8 While having the advantage of determining actual cost, relying on claims coding to identify patients and treatments is not without fault; 24.5% to 67.1% of patients identified by a diagnosis of cancer had no consequent identifiable treatment. 4,9,10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As possible explanation, the authors mention an increasing number of salvage surgeries and higher complications rates in the context of overall less performed interventions. In a retrospective study, Dedhia et al [166] demonstrated that the surgery costs accounted for an average of 24% of the whole hospital expenses while rooms, respiration therapy, laboratory, pharmacy, and radiology made up 38%, 14%, 8%, 7%, and 3%, respectively. In a model of decision analysis with data from studies, case series, and meta-analyses, Davis et al [167] came to the conclusion that total laryngectomy with postoperative radiotherapy costs nearly $ 3,000 less than induction chemotherapy followed by radiotherapy.…”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%